2020
DOI: 10.1016/j.bonr.2020.100717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotype of adult offspring carriers of the p.Pro392Leu mutation within the SQSTM1 gene in Paget's disease of bone

Abstract: Paget's disease of bone (PDB) is a common chronic bone disorder. In the French-Canadian population, the p.Pro392Leu mutation within the SQSTM1 gene is involved in 46% of familial forms. In New Zealand, the emergence of PDB in offspring inheriting SQSTM1 mutations was reported to be delayed by a decade compared to their parents. We aimed at assessing the clinical phenotype of offspring carriers of this mutation in our French-Canadian cohort. We reviewed research rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The mechanism of PDB pathogenesis however is similar since previous studies have shown that pathogenic variants in VCP can upregulate the NF-kB signaling pathway leading to upregulated osteoclastogenesis and bone resorption [7] and can therefore contribute to PDB [23,24,27]. Similarly, report of VCP's role in osteoblast activity involves complex regulation of bone morphogenetic protein (BMP) receptors via the VCP mediated ubiquitin/protein degradation system which may play a part in PDB pathogenesis [31,32]. Future studies should be considered to explore any pathological differences between the two entities.…”
Section: Discussionmentioning
confidence: 84%
“…The mechanism of PDB pathogenesis however is similar since previous studies have shown that pathogenic variants in VCP can upregulate the NF-kB signaling pathway leading to upregulated osteoclastogenesis and bone resorption [7] and can therefore contribute to PDB [23,24,27]. Similarly, report of VCP's role in osteoblast activity involves complex regulation of bone morphogenetic protein (BMP) receptors via the VCP mediated ubiquitin/protein degradation system which may play a part in PDB pathogenesis [31,32]. Future studies should be considered to explore any pathological differences between the two entities.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, VCP MSP1 is a rare disease, and this series represents a significant addition to the literature. Recent studies have reported intergenerational change of PDB phenotype in general population and those with SQSTM1 mutations 20 , 36 . In our study, we did not characterize these changes as our cohort is small although we anticipate a subsequent study characterizing the severity of PDB phenotype in MSP1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of PDB pathogenesis however is similar since previous studies have shown that pathogenic variants in VCP can upregulate the NF-kB signaling pathway leading to upregulated osteoclastogenesis and bone resorption 7 and can therefore contribute to PDB 16 – 18 . Similarly, report of VCP ’s role in osteoblast activity involves complex regulation of bone morphogenetic protein (BMP) receptors via the VCP mediated ubiquitin/protein degradation system which may play a part in PDB pathogenesis 19 , 20 . Despite the lack of treatment options for the neuromuscular and neurological manifestations of MSP1, treatment of PDB with bisphosphonates is very effective in alleviating bone pain, and preventing deformity and other comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, point mutations in p62 have been discovered in both Paget’s disease of bone (PDB) and ALS [ 82 , 83 ]. Notably, 25–50% of all familial PDB patients harbor mutations in p62, predominantly located in the UBA domain [ 84 , 85 ]. Among them, M404T and G411S mutants significantly impair p62 phase separation with multi-ubiquitin chains.…”
Section: Ubiquitin In Autophagymentioning
confidence: 99%